EFFECTIVENESS OF KUPANG SEA FLOUR GIVING AS ADDITIONAL FEED ON THE PRODUCTIVITY OF FREE-RANGE CHICKENS IN INCREASING FARMER INCOME - Abadi, Musram; Fatmawati, Fatmawati (Pascasarjana Universitas Sulawesi Tenggara, 2020)
Local chicken is one of the Indonesia native chickens that potential to be developed. It could be found in all the provinces from the city to the rural area though have the various weather and climate condition. Feed as one of the three main factors in animal field affect the improvement of animal production in fulfilling the animal protein needs of human. One of the alternatives to eliminate feed cost is utilizing local resources as protein sources for animal by using sea remis flour. This study aimed to understand the effectivity of sea remis flour addition on local chicken productivity. Research method used was completely randomized design consists of 4 treatments and 5 replications by using 40 laying phase local chickens raised intensively for 32 days in battery cages filled 2 chickens per cage unit. Treatment rations were concentrate substitution toward 0% of sea remis flour (R0), concentrate substitution toward 1.5 % of sea remis flour (R1), concentrate substitution toward 3% of sea remis flour (R2), concentrate substitution toward 4.5% of sea remis flour (R3). Based on result of the study, it could be stated that addition of 3% of sea remis flour in ration affect feed consumption, egg production, feed conversion, and egg weight.